KAJIAN POST-KOLONIALISME PADA MEDIA DALAM-RUANG DI JOGJA CITY MALL - Fatia Nurilmi Magistra (DeKaVe, 2019)
Media in non-Wester country has tendency to use various Western element as effect of culture system in which West is seen as the centre of culture. This manifests in various visual media in Indonesia, a country formed by ex-colonised archipelago of the Dutch, including in mal, a place designed to sell goods and services. This research attempts to observe visual indoor media in Jogja City Mall from post-colonial perspective, a perspective that studies the relation between powers, and see whether post-colonialism in the form of mimicry and hybridity forms there. Manifestation will be measured by how far the post-colonial effect exists and the reason why. Visual indoor media will be researched using case study, or more precisely cross-case study, a method chosen for the plentiful of the research population of indoor media in a mall. The research then shows that mimicry happened in indoor media and that it manifested because of the media’s context, or the mall as consumptive location, as where the media was placed.